(2x-4)/2=6x+3

Simple and best practice solution for (2x-4)/2=6x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-4)/2=6x+3 equation:



(2x-4)/2=6x+3
We move all terms to the left:
(2x-4)/2-(6x+3)=0
We get rid of parentheses
(2x-4)/2-6x-3=0
We multiply all the terms by the denominator
(2x-4)-6x*2-3*2=0
We add all the numbers together, and all the variables
(2x-4)-6x*2-6=0
Wy multiply elements
(2x-4)-12x-6=0
We get rid of parentheses
2x-12x-4-6=0
We add all the numbers together, and all the variables
-10x-10=0
We move all terms containing x to the left, all other terms to the right
-10x=10
x=10/-10
x=-1

See similar equations:

| 33-20y/7=1 | | (2x-4)/2=6x | | -30=5(x+5) | | x+214=434 | | 10x^2-3x=7 | | 6(x+2)+4x=42 | | -5(1-2x)+4(3-x)-7(3+x)=0 | | -6m-13=27 | | 5(4x-2)-9=21 | | 3x-3=5(x-4)+1 | | (x+2)/2=12/x | | x+19=4(x+1) | | 5x+4+54=180 | | 115+x+8=180 | | m=3.4=2.1 | | 10+v=17v=4 | | 14+2x=1.50x+20 | | 115+2x+9=180 | | 6=6x= | | X=6n+2 | | (5x-10)-(3x-3)=-1 | | 9d+2d+5d+6-6d=0 | | 1/2x-2=1/4x+5 | | 12x^2-44x+30=0 | | x+20+5x+4=180 | | 4(4x+1)=-44 | | (2,7)m=7 | | 16=2(x+3)-2 | | (2b-10)=3.2 | | v8+ 15= 20 | | 5x-22=2(x-4)-5 | | 2(5x+3)=3x-43 |

Equations solver categories